Pengaruh Pupuk Organik Cair Mucuna Bracteata dan Pupuk NPK Terhadap Pertumbuhan Kecambah Kelapa Sawit (Elaeis guineensis Jacq) di Pre-Nursery - Naima Yanti; Rizky Amnah; Erin Alawiyah Siregar (CIB Nusantara, 2025)
Oil palm (Elaeis guineensis Jacq.) is one of the most important plantation commodities in Indonesia's economy, with a lifespan of 20-25 years and a productive period of 10-20 years. Oil palm plants that are 20 years old are generally no longer productive and need to be rejuvenated (Replanting). This rejuvenation requires a large number of high-quality oil palm seedlings. The objective of this study was to determine the effect of the combination of Mucuna bracteata liquid organic fertilizer dose and NPK fertilizer dose on the growth of oil palm seedlings. This research was conducted from March to June 2025 in Partihaman Saroha village, Hutaimbaru District, Padangsidimpuan City. The research method used was an experimental method using a factorial randomized block design (RBD) with 2 treatment factors, the first being the concentration of Mucuna bracteata POC consisting of 3 levels: M0 (Control), M1 (20 ml/L), and M2 (40 ml/L), and the second being the concentration of NPK fertilizer consisting of 4 levels: PO (Control), P1 (0.08 g/polybag), P2 (0.12 g/polybag), P3 (0.16 g/polybag). The observed parameters were plant height (in cm), number of leaves (strands), stem diameter (in cm), and root length (in cm). Based on the research results, it shows that the application of Mucuna bracteata POC had no significant effect on all observed parameters, except for plant height at 12 WST. The best result was obtained with M2 at a concentration of 40 ml/L of water. The application of NPK fertilizer had no significant effect on all observed parameters, except for plant height at 12 WST. The best result was obtained in the P3 treatment = 0.16 g/polybag. There was no interaction between the combination of Mucuna bracteata POC and NPK fertilizer on the growth of oil palm seedlings.